Perbedaan Ekspresi Reseptor Hormonal Antara Pasien Premenopausal dan Postmenopausal Pada Kanker Payudara di RSUP H. Adam Malik Medan - Dippan Hutapea; Emir Taris Pasaribu; Suyatno Suyatno (Majalah Kedokteran Nusantara The Journal Of Medical School, 2016)
Introduction: Determination of Hormonal receptors is of utmost importance in planning therapy in patients with breast cancer. Breast cancer ussualy develops in perimenopausal and postmenopausal women and only several cases before age 25. Endogenous excess also plays role in the onset of breast cancer,  particularly in women with prolong reproduvtive periode, nulliparae, and those first delivery at an older age. The aim of the study was to assess the difference expression of estrogen receptors (ER) and progesterone receptors (PR) premenopausal and postmenopausal in breast cancer patient.Method :  This study  was analitic cross sectional included 245 patient treated at Oncology Surgery Division, Departemen of Surgery Medical Faculty USU – RSUP H. Adam Malik, between Januari 2013 until Mei 2015. ER and PR status was determine by Immunohistochemistry (IHC) from paraffin block.Result : From this researh the result of the premenopausal patients 137 (55.9%), postmenopausal 108 (44.1%). The frequency of premenopausal with ER + and PR +, 33 (24.1%) and postmenopausal 25 (23.1%). There was no significant different between ER and PR expression, tumor size and differentiation from histopathology grading between premenopausal and postmenopausal patient (p>0.05) in this research. And also in this research there was significant comparison between ER + PR + (Hormone dependent carsinoma) with premenopausal and postmenopausal with p value 0.043.Conclusion : From this research the hormonal expression receptor of ER and PR is higher in the premenopausal patient than the postmenopausal patient, but have no significant result in statistic.Keywords :  Estrogen Receptor, Progesteron Receptor, Premenopausal, Postmenopausal.